Identifikasi Bukaan Pada Fasad Bangunan Wisma Kilang Balikpapan, Indonesia - Huldiansyah, Denny (Prodi Arsitektur Universitas Matana, 2025)
Wisma Kilang Balikpapan remains the only surviving example of Jengki Architecture in Balikpapan City. This building stands as a silent witness to the city's dynamic development, evolving through the passage of time. It once flourished in the past, representing the diversity of architectural styles and unique designs that contributed to the modernization trends in Indonesia. However, this architectural style is nearing extinction due to modernization, marked by major renovations by the building's owners. This extinction poses a clear threat, with the possibility of the style gradually disappearing over time. This study aims to comprehensively and deeply identify and analyze the facade of Wisma Kilang Balikpapan, particularly focusing on the openings (doors, windows, and ventilation) as part of jengki architecture. It also examines the consistency and changes, both macro and micro, in the current facade as it interacts with changes in function, social and cultural contexts, and the surrounding environment. The research uses a qualitative descriptive method with a rationalistic paradigm to gather data and information about about the existing conditions of the building's openings in Wisma Kilang Balikpapan. The primary focus is on 6 units of the Wisma, with the identified elements including doors, windows, and ventilation. The study finds a variety of door, window, and ventilation types in Wisma Kilang Balikpapan, some of which remain intact, while others have changed. The facade's doors and ventilation tend to remain consistent, whereas windows have experienced significant alterations due to renovations and changes in building function. These findings can serve as a basis for building preservation policies and as a reference for future facade restoration efforts.